1996
DOI: 10.1002/j.1460-2075.1996.tb00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Single-stranded DNA binding protein and DNA helicase of bacteriophage T7 mediate homologous DNA strand exchange.

Abstract: Two proteins encoded by bacteriophage T7, the gene 2.5 single‐stranded DNA binding protein and the gene 4 helicase, mediate homologous DNA strand exchange. Gene 2.5 protein stimulates homologous base pairing of two DNA molecules containing complementary single‐stranded regions. The formation of a joint molecule consisting of circular, single‐stranded M13 DNA, annealed to homologous linear, duplex DNA having 3′‐ or 5′‐single‐stranded termini of approximately 100 nucleotides requires stoichiometric amounts of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 57 publications
1
68
0
Order By: Relevance
“…In addition to mere RNA replication, nsp9 could also participate in such a base-pairing-driven process as RNA processing. An informative parallel in the virus world is observed with bacteriophage T7: its gene 2.5 ssDNA-binding protein binds substrates with similar affinity as SARS-CoV nsp9 does [k d in the M range (37)] and is involved in replication͞recombination͞homologous basepairing events (38,39). The structural and functional characterization of nsp9 may also be relevant to SARS-CoV control: the SARS epidemics as well as previous work on CoVs have shown that genome plasticity (evolution by mutation and recombination) relate to pathogenicity and probably also to drug resistance.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to mere RNA replication, nsp9 could also participate in such a base-pairing-driven process as RNA processing. An informative parallel in the virus world is observed with bacteriophage T7: its gene 2.5 ssDNA-binding protein binds substrates with similar affinity as SARS-CoV nsp9 does [k d in the M range (37)] and is involved in replication͞recombination͞homologous basepairing events (38,39). The structural and functional characterization of nsp9 may also be relevant to SARS-CoV control: the SARS epidemics as well as previous work on CoVs have shown that genome plasticity (evolution by mutation and recombination) relate to pathogenicity and probably also to drug resistance.…”
Section: Resultsmentioning
confidence: 99%
“…The 63-kDa T7 gene 4 protein, a species of gene 4 protein that has both helicase and primase activities, was overexpressed and purified to apparent homogeneity (Ͼ98% pure) from E. coli cells by B. Beauchamp (Harvard Medical School) as described (22). T7 gene 2.5 protein was purified to apparent homogeneity (Ͼ98% pure) as previously described (2). T7 gene 6 protein (5Ј-to-3Ј exonuclease), E. coli single-stranded DNA-binding protein (SSB protein) and restriction enzymes were purchased from Amersham.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, we believe that the T7 gene 4 helicase-mediated strand exchange reaction provides the major pathway for recombination in E. coli cells infected with bacteriophage T7 (2). In the present study we have examined the ability of the T7 gene 4 helicase to participate in strand transfer reactions to produce heteroduplex molecules containing pyrimidine dimers, base pair mismatches, and insertions in each of the two DNA strands similar to those described above for the E. coli RecA protein.…”
mentioning
confidence: 93%
See 2 more Smart Citations